TESTING THE EFFICIENCY OF FENTONS REAGENT IN TREATMENT OF PETROLEUM-CONTAMINATED SAND - Millioli, Valéria S.; Freire, Denize D. C.; Cammarota, Magali C. (Revista de Engenharia Térmica, 2002)
The removal of petroleum of beach sand after an oil spill in Guanabara Bay, Rio de Janeiro (Brazil) was studied using Fentons reagent (Fe2+ + H2O2) with H2O2 concentrations of 0.4 M and 4.0 M and Fe2+ concentrations of 2.7 g/L and 27.2 g/ L. The initial Oil & Grease (O&G) content in the contaminated sand was 32 g/kg sand. The maximum O&G removal obtained was 97 % after Fentons reaction. An analysis of the supernatant after the reaction showed that it was biodegradable. Chromatographic analysis indicated that Fentons reaction favored the modification and reduction of the fractions of saturated and aromatic hydrocarbons in the oil.